2019
DOI: 10.29194/njes.22030208
|View full text |Cite
|
Sign up to set email alerts
|

Fresh, Mechanical Properties and Impact Resistance Behavior of Eco-Friend Self-Compacted Concrete

Abstract: In this work, waste glass powder from broken windows and plastic fibers from waste polyethylene terephthalate bottles are utilized to produce an economical self-compact concrete. Fresh properties (slump flow diameter, slump Flow T50, V. Funnel, L-Box), mechanical properties (Compressive strength and Flexural strength) and impact resistance of self-compact concrete are investigated. 15% waste glass powder as a partial replacement of cement with five percentages of polyethylene terephthalate plastic waste were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…However, for M4 mix with 20% of SSP the Max. γ dry has decreased while the OMC has increased, because of the increase in water content, and thus the w/cms ratio results in an increase of paste volume and porosity so, density will be decreased [29,32,33]. These results are in line with [31,32].…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…However, for M4 mix with 20% of SSP the Max. γ dry has decreased while the OMC has increased, because of the increase in water content, and thus the w/cms ratio results in an increase of paste volume and porosity so, density will be decreased [29,32,33]. These results are in line with [31,32].…”
Section: Resultssupporting
confidence: 79%
“…Figure 6 presents the f'c of control mix (M1), which has satisfied the specification requirement [50], in addition to the high quality (good density and lower voids) of the produced concrete as shown in Figures 7, 8 and 9. These results had obtained, although M-sand had used rather than conventional river sand [29,13,28,26,36]. The f'c results for all cubes that had tested in parallel // (as it had compacted) direction are higher than that of perpendicular (normal ꓕ) direction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Very few studies are found on the properties of chopped carbon fiber reinforced structural LWAC, including local pumice (Coarse and fine) as lightweight. Sheelan et al [8] explain the uses of chopped carbon fibers with different volume fractions (0.5%, 1%, 1,5%2%, and 2.5%) lengths of 6 mm to enhance the tensile strength of Porcelanite lightweight aggregate concrete. High-range water superplasticizers and silica fumes were used in the investigation.…”
Section: Original Researchmentioning
confidence: 99%
“…Many studies have been investigated the qualities of the hardness and fresh concrete including plastic materials [8][9][10][11][12]. Sheelan M. Hama, et al, [13] studied using waste water bottles made from polyethylene terephthalate (PET) as fiber form, manufacturing by self-compact concrete. PET fiber was used with five different content of (0.5%, 0.75%, 1%, 1.25% and 1.5%) by cement weight.…”
Section: Introductionmentioning
confidence: 99%